If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 4y = -12 Solving -4x + 4y = -12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. -4x + 4y + -4y = -12 + -4y Combine like terms: 4y + -4y = 0 -4x + 0 = -12 + -4y -4x = -12 + -4y Divide each side by '-4'. x = 3 + y Simplifying x = 3 + y
| u^2-8u+3=0 | | 6y-7y=18 | | 49c+31=26c-74 | | -2(5x-7)-(6x+15)= | | .25x^2+.5x=.75 | | 43.86+17.4= | | 6x-4=24 | | 5x+60-5=78+2x | | 6x-2(3-5x)=40 | | 100f-75=50f+75 | | 7x-11=19+3x | | 4a-26=82 | | 12y=88 | | (5s-4)(6s-6)= | | 5j=32.15 | | 2x^2-3x-50=0 | | 0.71x-0.31=10.25-5.89x | | 2y+12=100 | | 0.0022b=0.1958 | | 3t^2-8=0 | | 2x+13=2x+21 | | 3(8)+3(5+3)= | | 57k=0.1824 | | 10-x+2x=20 | | .75x-4=16 | | X+8=1x-18 | | 2(5-3x)+4=3(9x+7) | | (4a+4)(4a-4)= | | x^5-x^4-5x^3+5x^2+4x-4=0 | | 6-2y=9-6y+4y | | 60r-50=15r-5 | | v=-v-3 |